RADIONUCLIDIC IMPURITIES IN PERTECHNETATE SOLUTION ELUTED FROM 99mTc-CHROMATOGRAPHIC GENERATOR LOADED WITH 99Mo-FISSION PRODUCT - Sunarhadijoso Soenarjo; Adang Hardi Gunawan (Jurnal Kimia Terapan Indonesia, 1997)
Medical radioisotope of 99mTc was firstly produced in Indonesia through the nuclear reaction of 98Mo (n;y) 99Mo -> 99mTc. The separation of the resulting 99mTc from the postirradiated natural MoO3 was carried out by solvent extraction using methyl ethyl ketone. Instead of this method, Radioisotope Production Center (RPC) BATAN has routinely produced 99mTc-chromatographic generator loaded with 235U-flSsion-produced 99Mo to provide 99mTc. By such generator, 99mTc can be easily and repeatedly liberated in the form of pertechnetate by vacuum elution using saline solution. Some fission- produced radionuclides, however, potentially contaminate the pertechnetate fraction. Gamma spectrometric determination was carried out to evaluate the level of radionuclidic impurities contaminating 99mTc-pertechnetate solution eluted from 99mTc- chromatographic generator produced over a 10-month period in 1993 - 1994. Radioactivity yield of the resulting 99mTc was independent to the origin of the loaded 99Mo. The 99mTc-pertechnetatate fractions were frequently contaminated with 99Mo, 131I and 103Ru, but the contamination did not exceed maximum permissible level. The fluctuation of contamination level may be influenced by irradiation parameters and separation techniques applied to the production of the loaded 99Mo.